THE DEVELOPMENT OF MOBILE LEARNING INTERACTIVE MEDIA IN DISCRETE MATHEMATICS COURSE OF SEMESTER V STUDENTS - Dita Yuzianah (Universitas Labuhanbatu, 2023)
This study aims to develop mobile learning interactive media in fifth-semester students' discrete mathematics courses to motivate students in learning discrete mathematics material via mobile phones anywhere and anytime. The population in this study were all mathematics education students at Universitas Muhammadiyah Purworejo and the sample in this study were fifth-semester students. The subjects of this study were VB semester students, totaling 30 students of the mathematics education study program Universitas Muhammadiyah Purworejo for broad trial and VA semester for trials limited to 7 students. This type of research is developed with the ADDIE stages, Design, Development, Implementation, Evaluation, and feedback. The results of this study show that interactive mobile learning media in discrete mathematics courses for fifth-semester students is feasible to use. This can be seen from the validity test, both material and media validity is stated to be very feasible, practicality reaches a value of 3.70 which is stated to be very practical, and in terms of effectiveness 80% of students meet the predetermined minimum value of 75.Keywords: interactive media, mobile learning, discrete mathematics coursesÂ AbstrakTujuan penelitian ini adalah untuk mengembangkan media interaktif mobile learning pada matakuliah matematika diskret mahasiswa semester V sehingga mahasiswa dapat belajar materi matematika diskret melalui handphone dimanapun dan kapanpun. Subjek penelitian ini adalah mahasiswa semester VB yang berjumlah 30 mahasiswa program studi pendidikan matematika Universitas Muhammadiyah Purworejo untuk uji coba luas dan semester VA untuk uji coba terbatas yang berjumlah 7 mahasiswa. Jenis penelitian adalah pengembangan dengan tahapan ADDIE yaitu Analysis (Analisis), Design (Desain/perancangan), Development (Pengembangan), Implementation (Implementasi/ eksekusi), Evaluation (Evaluasi/ umpan balik). Hasil penelitian ini menunjukan Media interaktif mobile learning pada matakuliah matematika diskret mahasiswa semester V layak digunakan ini terlihat dari uji validitas baik validitas materi maupun media dinyatakan sangat layak, kepraktisan mencapai nilai 3,70 yang dinyatakan sangat praktis, dan dari segi ke efektifan 80% mahasiswa memenuhi nilai minimalyang suda ditentukan yaitu 75Kata kunci: media interaktif, mobile learning, matematika diskret